The Interactive Role of Strategic Consensus in the Relationship Between Strategic Conversation in Achieving Entrepreneurial Orientation- An Exploratory Study of the Opinions of a Sample of Workers in Private Banks in the Al-Najaf Governorate (Babylon, Al- - al-balaghee, Noor Sabah Jalil (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The goal of this study is to find out how the strategic consensus variable interacts with the strategic conversation and its dimensions (active leadership, participation in conversations, and awareness of individual communication tendencies) in order to promote an entrepreneurial mindset. This will be done by looking at correlations and direct and indirect effects between the research variables for the data collected by A group of bank employees in the province of Najaf Al-Ashraf (Babylon, Al-Mansour, and Al-Khaleej) were given the questionnaire form. There were 300 questionnaires sent out, and 282 were returned. Of the 272 returned questionnaires, 272 were right, giving a retrieval rate of 94%. The advanced statistical programme SPSS.25 and the statistical programme AMOS.23 were both used to look at it. Theoretical results showed that there is a lack of information about how strategic consensus affects the relationship between strategic conversation (SC) and achieving entrepreneurial orientation (EO) in businesses in general and among private bank workers in the province of Najaf Al-Ashraf (Babylon, Al-Mansour' Al-Khaleej) in particular. The results also showed that there was a connection between the strategic conversation and the desire to be an entrepreneur. The strategic consensus played a big, positive, and important part in this connection. This shows that the more the parts of the strategic talk between bank employees are paid attention to, the more this makes the employees more entrepreneurial. What the study suggested: Putting more emphasis on the different parts of the strategic conversation by staying in touch to find events that can help in understanding basic patterns of behaviour and structural aspects; and the need for the organisation to pay attention to the idea of an entrepreneurial orientation because it has positive effects on the individual, which shows in his desire to belong and stay alive through Do your best at your job.